Phase transfer of TiO2 nanoparticles from water to ionic liquid triggered by phosphonic acid grafting. Issue 44 (23rd October 2017) - Bhandary, R.; Alauzun, J. G.; Hesemann, P.; Stocco, A.; In, M.; Mutin, P. H.
Abstract : Hydroxylated TiO2 nanoparticles can be transferred from water to [Emim][NTf2 ] ionic liquid by reaction with a phosphonic acid bearing a cationic group; this phase transfer involves both grafting and anion exchange. Abstract : Controlling the interface between TiO2 nanocrystals and ionic liquids is of high fundamental and applied interest for energy storage and conversion devices. Phase transfer of nanoparticles from a synthesis medium to a processing or an application medium plays a significant role in nanotechnology. Here we demonstrate that surface modification with phosphonic acids bearing cationic end-groups can trigger the phase transfer of TiO2 nanoparticles from an aqueous sol to a typical water-immiscible ionic liquid, [Emim][NTf2 ]. The transfer involves both the grafting of the phosphonic acid moiety and the exchange of the counter ion of the cationic end-group by NTf2 anions, as demonstrated by solid-state NMR, elemental analysis and independent grafting and ion exchange experiments. Furthermore, the colloidal stability of the TiO2 sols in [Emim][NTf2 ] strongly depends on the hydrophobic character of the cationic end-groups.